Neuroinflammation as a Target for Intervention in Subarachnoid Hemorrhage - de Oliveira Manoel, Airton Leonardo; Macdonald, R. Loch (Frontiers in Neurology, 2018)
Aneurysmal subarachnoid hemorrhage (SAH) is a sub-type of hemorrhagic stroke associated with the highest rates of mortality and long-term neurological disabilities. Despite the improvement in the management of patients suffering from SAH and the reduction in case fatality in the last decades, disability and mortality remain high in this population. Brain injury can occur immediately and in the first days after SAH. This early brain injury can be due to physical effects on the brain such as increased intracranial pressure, herniations, intracerebral and intraventricular hemorrhage, hydrocephalus. After the first 3 days, angiographic cerebral vasospasm (ACV) is a common neurological complication that in severe cases can lead to delayed cerebral ischemia (DCI) and cerebral infarction. Consequently, the prevention and treatment of ACV was and continues to be a major goal. However, most treatments for ACV are vasodilators since ACV is due to arterial vasoconstriction. Other targets also have included those directed at the underlying biochemical mechanisms of brain injury such as inflammation and either independently or as a consequence, cerebral microthrombosis, cortical spreading ischemia, blood brain barrier breakdown and cerebral ischemia. Unfortunately no pharmacologic treatment directed at these processes has yet shown efficacy in SAH. Enteral nimodipine and the endovascular treatment of the culprit aneurysm, remain the only treatment options supported by evidence from randomized clinical trials to improve patients’ outcome. Currently, there is no intervention directly developed and approved to target neuroinflamation after SAH. The goal of this review is to provide an overview on anti-inflammatory drugs tested after aneurysmal SAH.